Environmental Conservation Values in an Early Childhood Curriculum Document: A Qualitative Content Analysis - Fani Astika; Yuli Kurniawati Sugiyo Pranoto; Petra Kristi Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2026)
Environmental conservation should be introduced in early childhood education through curriculum design, as curriculum documents shape children's learning experiences and value development. However, previous studies have primarily examined environmental education in classroom practice, with limited attention to how conservation values are represented within curriculum documents. This study aims to analyze the representation of environmental conservation values in an early childhood curriculum using four analytical dimensions: preservation, maintenance, management, and protection.This study employed a qualitative content analysis of one internal curriculum document from Ar Nature School. The document was analyzed through repeated reading, open coding, and deductive categorization. After removing repetitive and non-analytical content, 31 meaningful textual segments were identified and coded into four conservation dimensions. Analytical credibility was enhanced through iterative coding, constant comparison, analytical memos, and an audit trail.The findings reveal that conservation values are systematically embedded across the curriculum's four learning pillars—Morals, Leadership, Logical Thinking, and Business—despite the absence of explicit conservation terminology. Preservation and protection dominate the Morals pillar, maintenance characterizes Leadership, preservation and management are emphasized in Logical Thinking, and management is most prominent in the Business pillar. Together, these dimensions form an integrated ecological value system embedded in daily learning experiences.The curriculum promotes environmental conservation implicitly through moral development, experiential learning, and nature-based activities. This study contributes a four-dimensional analytical framework for examining conservation values in early childhood curriculum documents and highlights the importance of explicitly incorporating conservation terminology and ecological learning indicators to strengthen Education for Sustainable Development (ESD) implementation.